Development of a Simulated Environment for Human-Robot Interaction - Jochen Hirth; Syed Atif Mehdi; Norbert Schmitz; Karsten Berns (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
Human-robot interaction scenarios are extremely complicated and require precise definition of the environment variables for rigorously testing different aspects of robotic behavior. The environmental setup affects the behaviors of both the humans and the robots, as they respond differently under varying accoustic or lightning conditions. Moreover, conducting several experiments repeatedly with the humans as test subjects also causes behavioral changes in them and eventually the responses remain no longer similar to the already conducted experiments. Thus making it is impossible to perform interaction scenarios in a repeatable manner. Developing and using 3D simulations, where different parameters can be adjusted, is the most beneficial solution in such cases. This requires not only the development of different simulated robots but also the simulation of dynamic surroundings including the interaction partner. In this paper, we present a simulation framework that allows the simulation of human-robot interaction including the simulated interaction partner and its dynamics.